Applications of recombinant proteins in cultured meat production - Bárbara Flaibam; Gabriela Souza Alves; Esteban Ivan da Silva Vejar; Tatiana Barreto Rocha Nery; André Damasio; Rosana Goldbeck (Future Foods)
Cultured meat has emerged as a sustainable alternative to conventional animal protein sources, showing potential for addressing the food security challenges expected to arise in the coming decades. However, several obstacles still need to be overcome before cultured meat can be produced and commercialized on a large scale, including the development of serum-free culture media, the design of cell growth scaffolds, and the replication of sensory and nutritional attributes of conventional meat. Among these obstacles, the high cost of culture media and the dependence on animal-derived inputs produced in small volumes remain the most significant barriers to the upscaling of cultured meat, raising economic and ethical concerns. A promising solution to these challenges is precision fermentation, whereby microorganisms are used as ''cell factories'' to produce specific recombinant proteins and molecules that can be incorporated into culture media or final products. Recombinant proteins can reduce production costs and improve the sensory and nutritional characteristics of cultured meat, resolving the ethical and environmental concerns associated with traditional meat production. This review examines the potential of applying recombinant proteins to solve challenges associated with cultured meat processing.